Analisis Kinerja Paving Blok Berbasis Limbah Plastik terhadap Sifat Fisik dan Mekanik - Firman, Risman; Limbongan, Joey; Taufan, Muhammad Ali (Program Studi Teknik Kimia, Universitas Pamulang, 2026)
The increasing accumulation of non-degradable plastic waste has encouraged the development of sustainable construction materials. This study examines the physical and mechanical performance of paving blocks manufactured from plastic waste using plastic–sand compositions of 100%, 75%, 50%, and 25% based on the sand weight. The production process includes melting the plastic, mixing it with sand, compressing the mixture, and testing based on SNI 03-0691-1996. Compressive strength increases with a higher plastic content, with the 75% plastic mixture reaching 11.64 MPa, followed by 100% plastic at 10.82 MPa, while the 25% mixture reaches only 8.91 MPa. Water absorption decreases as plastic content rises, with the 100% plastic mixture showing the lowest value (0.27%) and the 25% mixture the highest (3.78%). Abrasion resistance was recorded highest in the 100% plastic mixture, with wear values of 0.037- 0.062 mm/min. Based on SNI 03-0691-1996, the use of high plastic proportions was found to enhance the wear resistance and mechanical performance of the paving blocks, thereby demonstrating the significant potential of plastic waste as a sustainable construction material